Diurnal activities of the desert-dwelling elephants in northwestern Namibia - Keith Leggett (Pachyderm)
The diurnal activities of desert-dwelling elephants (Loxodonta africana) in arid northwestern Namibia were monitored for five years (2002–2006) through the wet, cold dry and hot dry seasons. Desert-dwelling elephant activity changed from year to year and depended on rainfall and flood events. Three methods were used to collect activity data: two involved focal animals where individual elephants were monitored at five-minute intervals or continuously; the third involved a scan method that monitored individuals or groups at two-minute intervals. No statistical difference was observed in the data obtained by each method. Group activities investigated included feeding, water and social activities, resting and walking, while individual activities were further differentiated to include grazing, browsing, debarking, drinking, wallowing, dusting, resting in shade, resting in the open or sun, and the type of social interaction. These activities were analysed on an annual, seasonal and time-of-day basis. Annual variations in observed activities were probably due to variations in annual rainfall. Feeding activities were the major activities of desert-dwelling elephants, being similar throughout the year and occurring mainly during the 0700–1100 h and 1500–1700 h time periods. Similar proportions of time spent feeding (as a percentage) have been reported from several other African elephant populations; however, grazing rather than browsing was the dominant feeding activity. Defecation rates were lower than those reported for any other elephant populations in Africa, reflecting a lower volume of vegetation intake. Walking and social activities were at their maximum during the cold dry season when adult males came into musth and actively pursued receptive females, and declined in the hot dry and wet seasons. These activities were similar to those reported from Zimbabwe and Tanzania. Activities associated with water and resting increased to a maximum during the wet and hot dry seasons during the heat of the day (1100–1500 h). Water activities were higher than had been reported by any other study, while resting activities were lower than studies reported in Zimbabwe but similar to those in Uganda and Tanzania.